Romance of the rails : why the passenger trains we love are not the transportation we need - O'Toole, Randal (Cato Institute, 2018)
American transportation has undergone many technological revolutions, from sailing ships to steam ships, from passenger trains and urban rail transit to airplanes and automobiles. Normally, the government has allowed and even encouraged these revolutions, but for some reason the federal government is spending billions of dollars trying to preserve and build obsolete rail transit and passenger train lines, including high-speed trains that cost more but are less than half as fast as flying. O'Toole asks why passenger trains have been singled out, and whether this policy makes sense.